1987
DOI: 10.1111/j.1365-2494.1987.tb02126.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of subsequent mangement on the success of introducing white clover to an existing sward

Abstract: Two experiments, each lasting approximately 12 months, were carried out at North Wyke, Devon, in 1982-83 (A) and 1983-84 (B), to investigate various sward managements following oversowing of white clover {Trifolium repens, cv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…Can suitable management help the clover expand to provide a useful and productive component in a sward destined to be managed in future with reduced inputs? The results from the main investigation (Table 4) point to the value of cutting rather than grazing management to achieve this, as found in an earlier experiment at this station (Sheldrick et al, 1987b) and recognized in farm experience (Hailey, 1988 and personal communication). Surprisingly, the data from the off-station investigation did not confirm this difference.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Can suitable management help the clover expand to provide a useful and productive component in a sward destined to be managed in future with reduced inputs? The results from the main investigation (Table 4) point to the value of cutting rather than grazing management to achieve this, as found in an earlier experiment at this station (Sheldrick et al, 1987b) and recognized in farm experience (Hailey, 1988 and personal communication). Surprisingly, the data from the off-station investigation did not confirm this difference.…”
Section: Discussionsupporting
confidence: 57%
“…In Experiment B there was a greater annual yield of clover DM in the conservation treatment. Spring application of propyzamide in a previous experiment had increased (P<0-001) the proportion of clover DM in cut herbage, but had not significantly increased clover stolon length or dry weight per m^ (Sheldrick et al, 1987b), as in the experiments now reported. It was concluded from the earlier experiment, and much reinforced by highly variable individual site performance in the off-station investigations, that the effects of low-dose propyzamide when used to enhance clover contents is unpredictable and strongly influenced by the weather in the postspraying period.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…However, later on in the season the evidence suggests that a change of management involving a rest-period from grazing, may be necessary to increase the clover content of the sward. For example, improvements have been achieved by changing to a rotational system of grazing (Hay and Baxter, 1984), and also by incorporating a conservation cut (Wolton etal., 1970;Curll and Wilkins 1985;Sheldrick et al, 1987).…”
Section: Introductionmentioning
confidence: 99%